2020
DOI: 10.1111/pce.13705
|View full text |Cite
|
Sign up to set email alerts
|

Pst DC3000 infection alleviates subsequent freezing and heat injury to host plants via a salicylic acid‐dependent pathway in Arabidopsis

Abstract: Abiotic stresses greatly affect the immunity of plants. However, it is unknown whether pathogen infection affects abiotic stress tolerance of host plants. Here, the effect of defense response on cold and heat tolerance of host plants was investigated in Pst DC3000‐infected Arabidopsis plants, and it was found that the pathogen‐induced defense response could alleviate the injury caused by subsequent cold and heat stress (38°C). Transcriptomic sequencing plus RT‐qPCR analyses showed that some abiotic stress gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Indeed, despite their association with seemingly distinct biological processes (abiotic stress, biotic stress, and stem cell functions), a common denominator of functions of many C5 TFs may be growth restriction as a general response to stress. Clear examples of this include at least five cases: (1) the key cold stress adaptation factors CBF1 (At4g25490) and CBF2 (At4g25470) ( Liu et al, 2019 ), also shown recently to be induced by bacterial infection ( Tuang et al, 2020 ); (2) ERF017 (At1g19210) and ERF104, induced among other upon growth arrest-inducing intense light treatment ( Vogel et al, 2014 ); (3) ERF018/ORA47 (At1g74930) that has direct roles in control of biosynthesis of the growth-restricting phytohormones abscisic and JA, and whose overexpression causes slow growth ( Chen et al, 2016 ); (4) ANAC044 (At3g01600), important for arrest of cell division in response to DNA damage ( Takahashi et al, 2019 ); and (5) heat shock TFs HSFA3 (At5g03720) and HSFA6B (At3g22830) implicated in growth restriction and induction of chaperones destined to both cytoplasm and secretory pathways ( Schöffl et al, 1998 ; Guo et al, 2016 ). In this regard, we note that the uORF-skipping alternative TSSs induced in Hsp70 and the nucleotide exchange factor BAG6 ( Figure 6, A and B ) may be linked to the immediate induction of HSFs in C5 and C2 (HSFA4A (At4g18880), HSFB2A (At5g62020), Supplemental Data Set 9 ), and heat shock TFs as a group have previously been proposed to be major drivers of the growth-to-defense transition ( Pajerowska-Mukhtar et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, despite their association with seemingly distinct biological processes (abiotic stress, biotic stress, and stem cell functions), a common denominator of functions of many C5 TFs may be growth restriction as a general response to stress. Clear examples of this include at least five cases: (1) the key cold stress adaptation factors CBF1 (At4g25490) and CBF2 (At4g25470) ( Liu et al, 2019 ), also shown recently to be induced by bacterial infection ( Tuang et al, 2020 ); (2) ERF017 (At1g19210) and ERF104, induced among other upon growth arrest-inducing intense light treatment ( Vogel et al, 2014 ); (3) ERF018/ORA47 (At1g74930) that has direct roles in control of biosynthesis of the growth-restricting phytohormones abscisic and JA, and whose overexpression causes slow growth ( Chen et al, 2016 ); (4) ANAC044 (At3g01600), important for arrest of cell division in response to DNA damage ( Takahashi et al, 2019 ); and (5) heat shock TFs HSFA3 (At5g03720) and HSFA6B (At3g22830) implicated in growth restriction and induction of chaperones destined to both cytoplasm and secretory pathways ( Schöffl et al, 1998 ; Guo et al, 2016 ). In this regard, we note that the uORF-skipping alternative TSSs induced in Hsp70 and the nucleotide exchange factor BAG6 ( Figure 6, A and B ) may be linked to the immediate induction of HSFs in C5 and C2 (HSFA4A (At4g18880), HSFB2A (At5g62020), Supplemental Data Set 9 ), and heat shock TFs as a group have previously been proposed to be major drivers of the growth-to-defense transition ( Pajerowska-Mukhtar et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, despite their association with seemingly distinct biological processes (abiotic stress, biotic stress, stem cell functions), a common denominator of functions of many C5 transcription factors may be growth restriction as a general response to stress. Clear examples of this include at least five cases: (i) the key cold stress adaptation factors CBF1 (At4g25490) and CBF2 (At4g25470) (Liu et al 2019), also shown recently to be induced by bacterial infection (Tuang et al 2020), (ii) ERF017 (At1g19210) and ERF104, induced among other upon growth arrest-inducing intense light treatment (Vogel et al 2014), (iii) ERF018/ORA47 (At1g74930) that has direct roles in control of biosynthesis of the growth-restricting phytohormones abscisic and jasmonic acid, and whose overexpression causes slow growth (Chen et al 2016), (iv) ANAC044 (At3g01600), important for arrest of cell division in response to DNA damage (N. Takahashi et al 2019), and (v) heat shock transcription factors HSFA3 (At5g03720) and HSFA6B (At3g22830) implicated in growth restriction and induction of chaperones destined to both cytoplasm and secretory pathways (Schöffl, Prändl, and Reindl 1998; Guo et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research showed that cold stress cross-activates basal immunity against bacterial pathogen Pseudomonas syringae pv tomato DC3000 (Pst DC3000) though activating SA pathway and inhibiting of JA pathway (Wu et al, 2019). Interestingly this pathogen infection also cross-activates cold response and thus increase cold tolerance of host plants (Tuang et al, 2020). These investigations provide an idea to exploit immunity to increase plants abiotic stress tolerance.…”
Section: Introductionmentioning
confidence: 89%
“…In previous work, it was shown that bacterial pathogen Pst DC3000 infection cross-activates the cold response and thus increased cellular viability under freezing (Tuang et al, 2020). As the pathogen infection leads to serious disease to plants, it is not possible to use the infection to increase freezing tolerance of eld plants.…”
Section: Flg22 Treatment Alleviated the Injury Caused By Freezing In ...mentioning
confidence: 99%